The Effects of Additional Filtration on Image Quality and Radiation Dose in Cone Beam CT: An In Vivo Preliminary Investigation. (2nd March 2022) - Houfrar, Jan; Ludwig, Bjorn; Bister, Dirk; Nienkemper, Manuel; Abkai, Ciamak; Venugopal, Adith
Abstract : Purpose . The aim of this study was to investigate the effect of reduced radiation doses on the image quality of cone-beam computed tomography scans and the suitability of such imaging for orthodontics, oral surgery, dental implantology, periodontology, and endodontology. Materials and Methods . Cone-beam computed tomography scans of a live patient were performed using seven attenuation filters with increased thickness to decrease the effective radiation dose from 22.4 to 1.8  μ Sv, and the effects of different radiation doses on image quality were further analysed. Quantitative image quality was calculated using dedicated measures, such as signal and contrast-to-noise ratio and sharpness. A panel of five certified raters assessed the cone-beam computed tomography scans qualitatively. Nine anatomical structures relevant to dentistry were identified, and the overall acceptance was assessed. Results . Linear reduction of the effective radiation dose had a nonlinear effect on image quality. A 5-fold reduction in the effective dose led to acceptable quantitative and qualitative image quality measures, and the identification rate of dental anatomical structures was 80% or greater. The use of less than 40% of the reference dose was unacceptable for all dental specialties. Conclusions . The ideal radiation dose for specific diagnostic requirements remains a patient-related and specialty-related decision that must be made on an individual basis. Based on the results of this study, it is possible to reduce exposure in selected patients, and at the same time obtain sufficient quality of images for clinical purposes.